Nivolumab associated DRESS syndrome: A case report - Paudel, Upama; Parajuli, Sudip (Nepal Journal of Medical Sciences, 2025)
Nivolumab is an IgG 4 antibody against PD-1 approved for treatment of metastatic lung cancer.  We report a case of Drug rash with eosinophilia and systemic symptoms (DRESS) associated with Nivolumab therapy for lung carcinoma with metastasis to vertebra in a 55 -year-old male who presented with sudden onset of erythema involving more than 80% body surface area for 3 days after a week of treatment with Nivolumab. A diagnosis of DRESS was made based on temporal association of injection Nivolumab and appearance of skin lesion, and presence of eosinophils in dermis. The patient was started on prednisolone 70 mg per day based on the body weight along with other supportive measures. The case is being reported because of very few reports of DRESS induced by Nivolumab in the literature and is first case report from Nepal. A literature review on DRESS induced by Nivolumab is also done.